Isolation and Urease Activity Test of Bacteria for Calcium Carbonate (Calcite) Precipitation (Biocementation) in Soil - HANIES AMBARSARI; AFLAKHUR RIDLO (Microbiology Indonesia, 2018)
The use of bacterial calcium carbonate (calcite) precipitation (biocementation) has recently become popular as a ground-improvement technique. Ureolytic bacteria having highly urease activities were known to have important roles in calcium carbonate precipitation process. One of our research objectives is to isolate and to select as many as possible such ureolytic bacteria from Indonesian soils to be further utilized for calcium carbonate (calcite) precipitation process in the soil for strengthening the soil structure. Isolation was performed anaerobically in selective media containing 40% urea. Four isolates with different morphologies were purified and coded as TK1, TK2, TK3, and TK4. Each of them was tested for its urease activity either as a pure culture or as a mixture of several cultures. The urease activity was measured based on the ammonia concentration produced in the growth media up to 7 x 24 hours. It was known that isolate TK4 had the highest urease activity on week 6, whilst a mixture of isolate cultures coded as TKC did not show a better urease activity than the isolate TK4. Hence, it could be concluded that the isolate TK4 was the best candidate to be used for further research on the calcium carbonate (calcite) precipitation process (biocementation) to strengthen the soil structure.